FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Ayumi Rahma; Rita Mulyani (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2018)
Manager’s flexibity in choosing accounting policies and conflict between agent and principal create opportunities of earning management.The purpose of this study is to analize the impact of asymmetric information, leverage, firm size, and Profitability toward earning management with mangerial ownership as moderating variable. Eleven companies from property, real estate and buliding construction that listed on Indonesia Stock Exchange from 2012 to 2016 is used as sample. Panel data analysis is used to test the hypothesis with the help of Eviews 8 as statistical software. The results are asymmetric information and Firm size do not affect earning manaegement. On the other hand, this study finds that Leverage and Profitability affect earning management. Leverage has negative relaitonship with earning management and Profitability has a posititive realtionship with earning management. Moreover, managerial ownership able to moderate the effect of asymmetric information, leverage, firm size and profitability on earning management. Keywords: Earning Management, Asymmetric Information, Leverage, Firm Size, Managerial Ownership